Integrating intelligent agent in computer mediated instruction system - Zakaria, Azizi; Siraj, Fadzilah (2000)
Recent years have witnessed the deployment of thousands of web-based educational systems on the World Wide Web (WWW).However, majority of the systems consist of static hypertext pages that are non-interactive and non-adaptive.The challenge is to develop an advance web-based educational system integrating intelligent agent that offers interactivity and adaptability.Intelligent agent is a new class of software or 'SOFT ROBOT' that acts on behalf of the user by performing special task such as filtering email, negotiating for services, automating complex tasks, scheduling appointment, finding and filtering information and making travel arrangement.Intelligent agent has been predicted to be the most important computer paradigm in the next ten years.By the year 2000 every significance application would have some form of agent functionality.One of the most promising research areas for intelligent agent is education and training.Such an agent can be used specifically to support and guide interaction between the student and the system.This agent is referred to as pedagogical agent.Pedagogical agent is an autonomous agent that acts as virtual tutors or teacher to create rich, face to face learning interactions.It can also be represented as animated characters to make the learning process more lively and appealing.Animated pedagogical agent offers great promise for broadening the bandwidth of tutorial communication and increasing the ability of learning environment to engage and motivate students.This paper described PEAGENT, an interactive and adaptive web-based educational system integrating four animated pedagogical agents that communicate in Malay language and perform various pedagogical functions.